1989
DOI: 10.1139/p89-017
|View full text |Cite
|
Sign up to set email alerts
|

Study of multiplicity and the pseudorapidity correlation in the forward and backward hemisphere for pions and protons emitted in a 12C – emulsion interaction at 4.5 A ∙ GeV/c

Abstract: The paper presents an in depth study of the forward and backward pseudorapidity correlations for pions and protons produced in a 12C -emulsion interaction at 4.5 A . GeV/c. The angular distribution of protons and the pseudorapidity distribution of pions are pictured. The asymmetry parameter ( A ) and the forward -backward ratio ( F I B ) are shown as a function of the number of heavy particles (n,). L'article prCsente une Ctude en profondeur des corrilations de pseudorapiditC, vers l'avant et vers l'arrikre, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The backward emission of protons and pions in hadron-nucleus [1][2][3][4][5][6][7] and nucleus-nucleus [8][9][10][11][12][13][14][15][16][17][18] at relativistic energies have been investigated exclusively. It is found that the backward proton production was attributed to the absorption of secondary pions by a nucleon pair in the target nucleus, and the backward pions production shown to be consistent with the cumulative effect [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The backward emission of protons and pions in hadron-nucleus [1][2][3][4][5][6][7] and nucleus-nucleus [8][9][10][11][12][13][14][15][16][17][18] at relativistic energies have been investigated exclusively. It is found that the backward proton production was attributed to the absorption of secondary pions by a nucleon pair in the target nucleus, and the backward pions production shown to be consistent with the cumulative effect [19].…”
Section: Introductionmentioning
confidence: 99%
“…The study of the production of backward particles in hadron-nucleus and nucleus-nucleus interactions at high energies has received considerable experimental and theoretical attention because the fact that the backward emission of relativistic particles in high energy hadronnucleon collisions is kinematically restricted. The backward emission of protons and pions in hadron-nucleus [1][2][3][4][5][6][7] and nucleus-nucleus [8][9][10][11][12][13][14][15][16][17][18] at relativistic energies have been investigated exclusively. It is found that the backward proton production was attributed to the absorption of secondary pions by a nucleon pair in the target nucleus, and the backward pions production shown to be consistent with the cumulative effect [19].…”
Section: Introductionmentioning
confidence: 99%